Countries, national alcohol limits and risk behaviours: results from the TEN D by Night project (Epidemiology, Biostatistics, and Public Health, 2022)
Background: this paper re-analysed data from the international cross-sectional TEN-D survey to investigate the association between country or national alcohol limits and risk behaviours.Methods: data were collected on subjects aged 16-35 years owning a driving license and attending recreational sites during weekend nights in Belgium/Netherlands, Bulgaria, Italy, Poland and Spain. Each participant was administered a: questionnaire, driving simulation, breath alcohol concentration (BAC) and illegal drugs detection tests. Random-effect regression was used to identify independent predictors of 3 outcomes: high BAC (≥0.5 g/L); negative driving behaviours; self-reported illegal drug consumption.Results: the survey included 4 534 subjects (mean age 23.1±4.2 years; males 68.3%). Alcohol misuse was highest in Poland (65.1%) and Spain (83.7%), which also showed the highest frequency of negative driving behaviours (39.0%) and illegal drugs consumption (55.6%). Multivariate analysis confirmed country as a predictor of all outcomes, whereas no association was found with national alcohol limits.Conclusions: the absence of association between national alcohol limits and alcohol misuse or negative driving behaviours suggests that cultural factors might be predominant in explaining the differences across countries. Our findings are preliminary and further research is needed.